On A Modified SP-Iterative Scheme for Approximating Fixed Point of A Contraction Mapping - Z. Jamil, Zeana; B. Abed, Moamer (Iraqi Journal of Science, 2023)
In this paper, we will show that the Modified SP iteration can be used to approximate fixed point of contraction mappings under certain condition. Also, we show that this iteration method is faster than Mann, Ishikawa, Noor, SP, CR, Karahan iteration methods. Furthermore, by using the same condition, we shown that the Picard S- iteration method converges faster than Modified SP iteration and hence also faster than all Mann, Ishikawa, Noor, SP, CR, Karahan iteration methods. Finally, a data dependence result is proven for fixed point of contraction mappings with the help of the Modified SP iteration process.